Design of integrated balancing transformer for high frequency AC‐LED drive circuit. Issue 12 (1st June 2016) - Kang, B.G.; Choi, Y.; Chung, S.K.
Abstract : An integrated balancing transformer is proposed for a high frequency parallel AC‐LED drive circuit using a LLC resonant converter. The design and implementation of the integrated balancing transformer are presented. The experimental results for the converter with the integrated transformer are provided to show the validity of the proposed technique.